Slope stability analysis using GIS on a regional scale - Kayastha, P (Journal of Nepal Geological Society, 2008)
Stability of land is indispensable for the safety of human life and development of infrastructure. Landslides are the most common natural hazards in Nepal, where about 83% of the area are in the mountainous and hilly regions. In this study, a slope stability analysis on a regional scale is presented for a area of 347 km2 of Dhading district, Nepal. A physically based slope stability model coupled to a simplified groundwater flow model is used to estimate soil wetness index, and factor of safety maps are produced for three steady state scenarios (completely dry, half-saturated, and completely saturated soils) and one quasi-dynamic scenario (soil wetness resulting from extreme daily rainfall events with return periods of 25 years) with both methods based on infiltration and contributing area. One model is developed from these three steady state scenarios. These models help the engineers and planners to apply landslide hazard models on a regional scale to the regions that generally lack advanced information systems with the presented methodology and basic GIS tools. The quantitative relation ships between stability and factors affecting stability are established by the Certainty Factor (CF) model. The affecting factors such as land use pattern, soil types and steepness (slope type) are recognized. From CF value, the most significant factors are selected. Based on the model developed on the basis of three steady state scenarios, 27.71 of the research area is unconditionally stable and 0.59 of the research area is unconditionally unstable. According to the results of three steady states and one quasi-dynamic state model, there is a decrease in stability from completely dry condition to completely saturated condition. In all scenarios, very steep slope area (slope angle more than 300) contributes to areas prone to failure. In addition, areas having poorly graded gravel and clayey gravel have more effect in instability of slope than those areas having other types of soils. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.19